2015
DOI: 10.1186/s12902-015-0033-2
|View full text |Cite
|
Sign up to set email alerts
|

Two-year assessment of the efficacy and safety of sitagliptin in elderly patients with type 2 diabetes: Post hoc analysis of the ASSET-K study

Abstract: BackgroundThere have only been a few reports about use of dipeptidyl peptidase 4 (DPP-4) inhibitors in elderly patients with type 2 diabetes mellitus (T2DM), suggesting that the safety of these agents has not been sufficiently demonstrated. We performed a comparative review of the efficacy and safety of sitagliptin for Japanese patients with T2DM managed in the real-world clinical setting.MethodsAn age-stratified analysis was performed of 831 patients who were treated with sitagliptin for 2 years. Parameters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 31 publications
10
33
0
2
Order By: Relevance
“…The AE profiles for which a causal relationship to the study drug could not be excluded were similar between the sitagliptin group and the glimepiride group during the 104 weeks. The results for AEs and serious AEs in this trial were essentially consistent with the safety profile of sitagliptin reported in pooled analyses of 25 sitagliptin studies in elderly patients with T2DM and a 2‐year observational study of the efficacy and safety of sitagliptin in elderly Japanese patients with T2DM …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The AE profiles for which a causal relationship to the study drug could not be excluded were similar between the sitagliptin group and the glimepiride group during the 104 weeks. The results for AEs and serious AEs in this trial were essentially consistent with the safety profile of sitagliptin reported in pooled analyses of 25 sitagliptin studies in elderly patients with T2DM and a 2‐year observational study of the efficacy and safety of sitagliptin in elderly Japanese patients with T2DM …”
Section: Discussionsupporting
confidence: 85%
“…The results for AEs and serious AEs in this trial were essentially consistent with the safety profile of sitagliptin reported in pooled analyses of 25 sitagliptin studies in elderly patients with T2DM 15 and a 2-year observational study of the efficacy and safety of sitagliptin in elderly Japanese patients with T2DM. 16 The present study has several limitations. First, when the study was started in 2010, the target patient number was 540, a number that should allow proof of the study hypothesis with a probability of 93%; however, the study was terminated in 2015 after enrolling 305 patients because of difficulty in patient recruitment.…”
mentioning
confidence: 83%
“…Thus, they have become important treatment options for patients in Japan, including the elderly, often as first-line therapy [6][7][8]. Glucagon-like peptide-1 (GLP-1) receptor agonists are also incretin-based and have similar safety and better efficacy profiles in patients with T2D compared to DPP-4 inhibitors [4][5].…”
mentioning
confidence: 99%
“…We have shown a similar reduction in HbA1c after treatment for 12 months with sitagliptin as previous reports on DPP-4 inhibitors in patients aged ≥75 years, [12][13][14] and a previous analysis of participants in three groups, as with our present study. 15 A previous analysis showed that older patients, short duration of diabetes and high baseline HbA1c were the factors that influenced the change in HbA1c after 12 months of sitagliptin therapy. 16 Nevertheless, baseline HbA1c was the lowest in the ≥75 years age group in the present study, although improvement in HbA1c was not significantly different among the three age groups.…”
Section: Discussionmentioning
confidence: 98%